Spatio-temporal distribution of soft-bottom epibenthic fauna on the Cilician shelf (Turkey), Mediterranean Sea - Mutlu, Erhan; Betil Erguev, Mehmev (Revista de Biología Tropical, 2008)
Spatio-temporal distribution of epifauna collected with a sledge was studied on the Cilician shelf of the Mediterranean Sea. There were two different communities: the shallow community was restricted to water at 5 and 10 m deep with sandy bottom inhabited abundantly by Conomurex persicus, Arnoglossus laterna and Murex trunculus. Conomurex persicus, an introduced tropical species predominated the shallow zone and distinguished it from the deep zone. The deep community (25-150 m) lacked shallow water species and was dominated by Arnoglossus laterna, Goneplax rhomboides and Parapenaeus longirostris. Seasonality was not a major factor in the epibenthic community structure of the entire shelf, but it is in the shallow waters. Bottom depth was main factor for structuring the community on the shelf. Sediment size and organic content is also a controlling factor for the distribution of the epibenthic fauna.